Strengthening Water Governance and Regulatory Effectiveness for Equitable Access in Indonesia - Pambudi, Andi Setyo; Pramujo, Bambang (Jurnal Pemerintahan dan Politik Lokal, 2025)
Water resource management in Indonesia represents a paradox of abundance and scarcity. Despite the country’s vast hydrological potential, approximately 15% of Indonesians still lack reliable access to clean water, with stark inequalities persisting between urban and rural regions. Prior research has primarily emphasized technical and infrastructural dimensions, leaving a research gap in understanding how regulatory frameworks intersect with socio-economic and environmental realities. The urgency of this study stems from persistent disparities in water accessibility, escalating climate change pressures, and weak enforcement of existing laws such as Law No. 17 of 2019 on Water Resources. This study aims to evaluate the effectiveness of regulatory instruments in expanding water accessibility, identify determinants shaping implementation, and assess broader sustainability implications. Employing a qualitative descriptive method with case studies in West Java, East Nusa Tenggara, and South Kalimantan, data were collected through document analysis, in-depth interviews, and field observations. The findings indicate that regulatory effectiveness is heavily influenced by geographic and institutional contexts, with challenges ranging from infrastructural deficits to pollution and climate-induced scarcity. The study recommends adaptive, region-specific regulations, strengthened institutional capacity, and participatory governance to ensure equitable and sustainable water access.